2009
DOI: 10.2174/1875934300902010026
|View full text |Cite
|
Sign up to set email alerts
|

Does Safety Training Reduce Work Injury in the United States?

Abstract: Using a cross-sectional model, this paper analyzes the relationships between occupational injury rates and worker safety training, workplace safety practices, and health-oriented employee benefits in the United States. We merged U.S. Bureau of Labor Statistics establishment-level data on employee training, benefits, and rates of occupational injuries and illnesses with days away from work, obtaining a data set on 2,358 establishments, 62% of them with at least 250 employees. Weighted two-stage regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
3
17
1
Order By: Relevance
“…This singular factor could not have made the implementation of such accident control programmes viable in Nigerian industries. Also, this current study did not support the submission of Geetha & Ted (2009) that safety training is more effective in large firms, because a 90% of manufacturing industries used in this study are large firms and yet, training was not found effective.…”
Section: Discussion Of Findingscontrasting
confidence: 72%
See 1 more Smart Citation
“…This singular factor could not have made the implementation of such accident control programmes viable in Nigerian industries. Also, this current study did not support the submission of Geetha & Ted (2009) that safety training is more effective in large firms, because a 90% of manufacturing industries used in this study are large firms and yet, training was not found effective.…”
Section: Discussion Of Findingscontrasting
confidence: 72%
“…Inadequacy of safety equipment, as found in industries (Eboh & Onohwakpor, 2002) and universities (Ayodele, 2012) where these researchers conducted their studies could render safety education in the two settings ineffective. Not outrightly faulting education and training as measures of preventing accidents, Geetha and Ted (2009) said that such training is more effective in large firms but less effective in small firms. Michael, Sue, Kristin, Suzanne, Rommel and Gazi (2006) found that less engaging approaches to safety training like lectures and computer-based trainings yielded low result when compared to more engaging approaches like hand-on-trainings.…”
mentioning
confidence: 99%
“…Traditional solutions, involving administrative controls such as training and policies, have had minimal long-term impact on the incidence and severity of overexertion injuries associated with MMH [37, 38]. Engineered solutions in the form of mechanical assist or lift devices are commonly used in large production and construction businesses, yet few, if any, of these assist devices have found their way into retail businesses during the past 30 years [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the finding that migrants were injured more often at industrial (p \ 0.0001) site suggests that this is due to work in risky settings and in low-skill occupations, temporary employment conditions [2,16], reduced communication owing to incapability to speak Hebrew, lack of training [8,17,18], low education, cultural norms and attitudes about vulnerability and prevention and other socioeconomic factors. As there is evidence that safety training reduces workplace injuries [19][20][21], safety training and work-related guidance is desirable for migrant employees to perform their work in safety, and the safety training should be adapted to the needs of these workers, that are most at risk for traumatic injuries. Communication with migrant workers can be a problem, due to language barriers.…”
Section: Discussionmentioning
confidence: 99%